The Gentle Side of the UPS: Ubiquitin-Proteasome System and the Regulation of the Myogenic Program - Olguín, Hugo C. (Frontiers in Cell and Developmental Biology, 2022)
In recent years, the ubiquitin-proteasome system (UPS) has emerged as an important regulator of embryonic stem cell pluripotency and differentiation capacity. Here we review recent findings indicating that UPS also plays critical roles in the biology of satellite cells, the tissue-specific skeletal muscle stem cells responsible for muscle maintenance and regeneration. While we focus our attention on the control of key transcriptional regulators of satellite cell function, we briefly discuss early studies suggesting the UPS participates more broadly in the regulation of satellite cell stemness, heterogeneity, and aging.